A2B Adenosine Receptors and Sphingosine 1-Phosphate Signaling Cross-Talk in Oligodendrogliogenesis - Coppi, Elisabetta; Cencetti, Francesca; Cherchi, Federica; Venturini, Martina; Donati, Chiara; Bruni, Paola; Pedata, Felicita; Pugliese, Anna Maria (Frontiers in Neuroscience, 2021)
Oligodendrocyte-formed myelin sheaths allow fast synaptic transmission in the brain. Impairments in the process of myelination, or demyelinating insults, might cause chronic diseases such as multiple sclerosis (MS). Under physiological conditions, remyelination is an ongoing process throughout adult life consisting in the differentiation of oligodendrocyte progenitor cells (OPCs) into mature oligodendrocytes (OLs). During pathological events, this process fails due to unfavourable environment. Adenosine and sphingosine kinase/sphingosine 1-phosphate signalling axes (SphK/S1P) play important roles in remyelination processes. Remarkably, fingolimod (FTY720), a sphingosine analogue recently approved for MS treatment, plays important roles in OPC maturation. We recently demonstrated that the selective stimulation of A2B adenosine receptor (A2BARs) inhibit OPC differentiation in vitro and reduce voltage-dependent outward K+ currents (IK) necessary to OPC maturation, whereas specific SphK1 or SphK2 inhibition exerts the opposite effect. During OPC differentiation A2BAR expression increases, this effect being prevented by SphK1/2 blockade. Furthermore, selective silencing of A2BAR in OPC cultures prompts maturation and, intriguingly, enhances the expression of S1P lyase, the enzyme responsible for irreversible S1P catabolism. Finally, the existence of an interplay between SphK1/S1P pathway and A2BARs in OPCs was confirmed since acute stimulation of A2BARs activate SphK1 by increasing its phosphorylation. Here the role of A2BAR and SphK/S1P signalling during oligodendrogenesis is reviewed in detail, with the purpose to shed new light on the interaction e between A2BARs and S1P signalling, as eventual innovative targets for the treatment of demyelinating disorders. Keywords: adenosine, A2B receptors, oligodendrocyte progenitor cells, sphingosine-1-phosphate, oligodendrocyte differentiation, K+ channels, remyelination, sphingosine kinase.